1990
DOI: 10.1002/arch.940150302
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of Blattella germanica vitellin during early embryo development

Abstract: In the eggs of the cockroach Blattella germanica, vitellin (Vt) utilization i s initiated 4 days postovulation by the proteolytic processing of its three subunits. These reactions yield a specific set of peptides that are consumed by the developing embryo. A yolk proteinase activity, believed central to this processing event, has been investigated. First expressed at day 3 postovulation, just prior to Vt's processing, its specific activity with synthetic substrates increased fourfold to 18-fold through day 6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
3
28
0
1
Order By: Relevance
“…Similar processing events are characteristic of Vt utilization in other insect species also (see Ref. 9, and references therein).…”
supporting
confidence: 63%
See 3 more Smart Citations
“…Similar processing events are characteristic of Vt utilization in other insect species also (see Ref. 9, and references therein).…”
supporting
confidence: 63%
“…Previous work demonstrated that Vt utilization in Blattella germanica eggs is initiated at days 3-4 postovulation by proteolytic processing to a distinct set of peptides, which are then accessed by the embryo during development (9,15,16). Similar processing events are characteristic of Vt utilization in other insect species also (see Ref.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Insect embryos develop by utilizing a store of maternally derived proteins or vitellins (Nordin et al 1990;Giorgi et al 1999). These proteins are deposited in the oocyte during ovarian development as high molecular weight precursors or vitellogenins (Vg) by a process of receptor-mediated endocytosis (Raikhel 1984;Sappington et al 1995;Mellman 1996;Snigirevskaya et al 1997).…”
Section: Introductionmentioning
confidence: 99%